On black children in black families - Wilbraham, Lindy (PINS-Psychology in Society, 2017)
[BOOK REVIEW] Makiwane, Monde, Nduna, Mzikazi & Khalema, Nene, E (eds) (2016) Children in South African families: Lives and times. Newcastle-upon-Tyne: Cambridge Scholars Publishing. ISBN 978 1 4438 9735 8 hbk. Pages 320 Theorising healthy development of children, identifying troubling “obstacles” to their thriving, and intervening in appropriate ways to support and monitor well-being is never neutral work. Over the years, given the inequities and injustices of colonial and apartheid apparatuses in South Africa, there has been a lot of attention given – by social scientific academics, researchers, activists and policymakers – to children and families. This attention has focused most notably on black children and families, living in everyday conditions of adversity, vulnerability and risk, and has incorporated various theoretical lenses and advocacy for interventions.